Modified melamine-formaldehyde resins improve tensile strength along with antifouling and flame retardancy in impregnation of cellulose paper. Issue 63 (12th November 2019) - Chen, Xiaoyan; Afreen, Shagufta; Yu, Xiao; Dong, Chaohong; Kong, Qingshan
Abstract : Polyvinyl alcohol (PVA) and benzoguanamine (BG) modified melamine-formaldehyde (MF) resins were used to prepare high-pressure laminates (HPLs) and the improved tensile strength, flame retardancy and antifouling properties were investigated. Abstract : In this study, polyvinyl alcohol (PVA) and benzoguanamine (BG) modified melamine-formaldehyde (MF) resins were used to prepare two high-pressure laminates (HPLs) as well as a pure cellulose paper laminate and core sandwich laminates with the core material of aramid paper (AP) or polypropylene non-woven fabric (PPNF). The tensile strength, flame retardancy and antifouling properties of the modified MF resin laminates were studied and compared with the MF resin laminate. The tensile test results showed that the MF resins modified with BG and PVA improved the tensile strength of the impregnated paper. In comparison with pure kraft cellulose paper laminates, the aramid paper core laminates displayed comparatively higher tensile strength. Antifouling test results indicated that modified MF resin laminates had no obvious change while the MF resin laminate was stained. Thermal stability of the modified resins was investigated by thermogravimetric (TG) analysis and the results showed that the char yield of modified MF resin was higher than that of the unmodified MF resin due to the addition of BG. The modified MF resin laminates exhibited better flame retardancy properties through the analysis of limiting oxygen index (LOI), vertical burning and cone calorimetry (CONE) compared to the MF resin laminate. In addition, the flame retardancy of laminates was further enhanced when prepared with core materials of aramid paper. Scanning electron microscopy analysis of residue char after CONE tests showed that the AP-core laminate formed a dense and stable char layer compared with the loose char layer of the PPNF-core laminate. This study shows a new direction to develop sustainable high-performance flame retardant laminates for commercial decoration application.